Envisioning African Intersex Challenging Colonial and Racist Legacies in South African Medicine - Swarr, Amanda L. (Duke University Press, 2023)
Amanda Lock Swarr debunks the centuries old claim "hermaphroditism" and intersex are disproportionately common among black South Africans by interrogating how contemporary intersex medicine its indivisibility from colonial ideologies and scientific racism.